DUKUNGAN DAN PERSEPSI MASYARAKAT TERHADAP WACANA PEMEKARAN RUMBAI TAHUN 2014 - Yani Wahdini; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Regional divisions do not automatically provide prosperity for the region as mandated by laws and regulations and decentralization. expansion success stories tend to be less when compared with the current reality, many negative impacts of the expansion area. District of Rumbai desire to secede from the city of Pekanbaru ignited from uneven development reasons. and in terms of the administrative and technical requirements. Tassel not feasible to secede from the city of Pekanbaru. Tassel bloom always echoed in one of the mass media ie newspapers Riau many community newspapers and community leaders who support Rumbai to bloom, but after research conducted by the author turns largely Tassel community do not support the expansion of the Rumbai. of the phenomenon researchers are keen to gauge support and public perception in discourse Tassel expansion plan with the title "the support and the perception public the discourse of division Rumbai". Which became the basis of the problem where after doing field research, the authors found that support the expansion plan Rumbi only 46% while 54% do not support . Many people actually do not approve Rumbi division occurs, but sebahagian public figure and the originator of the division continued to echo the expansion plan Tassel, without knowing more in natural resources and human resources Rumbai. Theory (approach) that I use as a tool of analysis in this research is the theory of the Expansion of Regional and community participation, whereas the method used is a combination of quantitative and qualitative methods (mixed methods). Namely data collection techniques by Random sampling by taking a random sample of the entire community Rumbai andRumbaipesisir. Conclusions of this study is the emergence of a discourse division Rumbai not fully aspirations of its people, but there are other interests of the candidates to get voice support in legislative elections in 2014 by ignoring some of the process PP 78 in 2007. Key words: Community Participation, Public Perception and Discourse Regional Expansion